A novel process for copper protection in the simulated industrial cooling water based on click synthesis and self‐assembling method. Issue 11 (28th May 2019) - Li, Jin; Zhang, Daquan; Zhang, Kai; Gao, Lixin; Shi, Cheng; Chen, Donghui; Huang, Manhong
Abstract : The triazole inhibitor of 1‐(p‐tolylthio)‐1H‐1, 2, 3‐triazole‐4‐carboxylic acid (TTC) was synthesized via the Cu(I)‐catalyzed azide‐alkyne 1, 3‐dipolar cycloaddition reaction. The self‐assembling method was performed to fabricate the self‐assembled film of TTC on the copper surface. The electrochemical measurement results indicate that the TTC film can efficiently protect the copper from corrosion in high concentrated industrial cooling water. The protection efficiency of TTC film for copper is 92.2%. Surface characterizations imply that the copper with TTC film after corrosion is covered with multiple protective layers. It probably contains Cu(I) and Cu(II) complexes mixed with nitrogenous compound, Cl − and SO4 2− . The result of quantum chemical calculation shows that the superior performance of TTC film is related to the adsorption of TTC molecules on copper surface horizontally. This kind of adsorption is mainly achieved via the adsorption centers of triazole ring and O atoms in TTC molecule. Abstract : The click chemistry reaction was used to synthesize the triazole inhibitor. The self‐assembling method was then performed to fabricate inhibitive film of the triazole inhibitor on a copper surface. The triazole film can efficiently protect the copper from corrosion in high concentrated circulating cooling water. The superior protection performance is mainly achieved by the formation of multiple protective layers on the copper surface.